The Impact of ESG Score on Financial Performance: A Study on Banks Listed on the NASDAQ - KILIÇ, Gökhan; KIZILTAN IŞIK, Burçak; HABERAL, Zehra (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) scores on the financial performance of NASDAQ-listed banks. It examines whether ESG scores are associated with better financial performance, as measured by Return on Assets (ROA) and Return on Equity (ROE), between 2010 and 2021. In addition, the study aims to provide practical guidance for bank managers, investors, and policymakers on the strategic importance of ESG integration in the banking sector. In this study, a panel regression analysis was conducted using data on 74 banks with ESG scores. ROA and ROE are examined as dependent variables, and ESG scores are treated as the primary independent variable. ROA and ROE are significantly affected by ESG scores, implying that better financial results for banks are associated with higher levels of corporate social responsibility. Despite the low average ESG ratings in our sample, improving these ratings moderately improves profitability even for the low-rated banks included in our sample. In order to increase profits and gain a competitive advantage, banks may be wise to include environmental, social, and governance issues in their strategic plans. Investors should benefit from such ESG ratings when deciding on their investments. This study contributes to the growing literature on the financial effects of ESG performance by providing empirical evidence from a unique dataset of NASDAQ-listed banks. Despite the traditionally low emphasis on ESG in the banking sector, it provides new insights into the positive role that ESG integration can play in improving bank profitability.